KONSEP TABAYYUN DALAM AL-QURAN ANALISIS TERHADAP FENOMENA PENYEBARAN HOAX DI MEDIA SOSIAL - Samsir, Samsir; Yusril, Muhammad (TAFASIR: Journal of Quranic Studies, 2024)
This study examines the concept of tabayyun in the Quran and its importance in relation to the rampant phenomenon of spreading hoaxes on social media. The issue of hoaxes has emerged as a significant threat to social stability and interfaith harmony in the digital era. This research uses a qualitative methodology with a thematic interpretation approach, this research analyzes the verses of the Quran with a special focus on the sixth verse of Surah Al-Hujurat.  Data collection is done through literature review by examining books of tafsir, and contemporary sources on social media. The results of this study show that: (1) The Quran has established a comprehensive framework for information verification through the concept of tabayyun, (2) The application of tabayyun in the digital era requires source verification, content analysis, and impact assessment; (3) There is a strong relevance between the concept of tabayyun and efforts to counter fake news, This study concludes that the concept of tabayyun in the Quran presents a solution to overcome the problem of fake news (hoax) on social media.